O bairro planejado Urbanova, São José dos Campos: transformação de tecido urbano, pelas bordas da cidade, entre 1970 e 2019 - Alves, Adriana Thaís da Silva (2020)
The present research proposes to study the transformation and urbanization process of the Urbanova neighborhood, located in the São José dos Campos western area, during the period from 1970 to 2019. Such period comprises since the idealization of a neighborhood planned from a plan director coordinated by the architect Jorge Wilheim, pass trought spatial transformations conducted by public and private agents, until the forms of urban fabric configuration present nowadays and out of step with the initial plan: predominance of residential use and low density characterized by closed allotments turned for the higher income classes, besides considering a mobility model based on individual transport. In this regard understanding that cities are fundamental to the global transformation on the path of sustainability and out of the elements brought about by the research of Jorge Wilheim's plan, an analysis is necessary to contribute to the urbanization debate experiences experienced nowadays, the socio-spatial dynamics, the dichotomies, the burdens and the potential of the forms of dispersed intra-urban configuration, in contrast to the trend of new centralities with planned neighborhoods.